Performance Assessment of New Urinary Translational Safety Biomarkers of Drug-induced Renal Tubular Injury in Tenofovir-treated Cynomolgus Monkeys and Beagle Dogs. (July 2018) - Gu, Yi-Zhong; Vlasakova, Katerina; Troth, Sean P.; Peiffer, Robert L.; Tournade, Herve; Pasello dos Santos, Flavia R.; Glaab, Warren E.; Sistare, Frank D.
Newer urinary protein kidney safety biomarkers can outperform the conventional kidney functional biomarkers blood urea nitrogen (BUN) and serum creatinine (SCr) in rats. However, there is far less experience with the relative performance of these biomarkers in dogs and nonhuman primates. Here, we report urine protein biomarker performance in tenofovir-treated cynomolgus monkeys and beagle dogs. Tenofovir intravenous daily dosing in monkeys for 2 or 4 weeks at 30 mg/kg/day resulted in minimal to moderate tubular degeneration and regeneration, and tenofovir disoproxil fumarate oral dosing in dogs for 10 days at 45 mg/kg/day resulted in mild to marked tubular degeneration, necrosis, and regeneration. Among biomarkers tested, kidney injury molecule 1 (Kim-1) and clusterin (CLU) clearly outperformed BUN and SCr and were the most reliable in detecting the onset and progression of tenofovir-induced tubular injury. Cystatin C, retinol binding protein 4, β2-microglobulin, neutrophil gelatinase–associated lipocalin, albumin, and total protein also performed better than BUN and SCr and added value when considered together with Kim-1 and CLU. These findings demonstrate the promising utility of these urinary safety biomarkers in monkeys and dogs and support their further evaluation in human to improve early detection of renal tubular injury.